Competitive Entry and Endogenous Risk in the Foreign Exchange Market - Hau, Harald (Review of Financial Studies, 1998)
Recent evidence shows that higher trader participation increases exchange rate volatility. To explore this linkage, we develop a dynamic model of endogenous entry of traders subject to heterogenous expectational errors. Entry of a marginal trader into the market has two effects: it increases the capacity of the market to absorb exogenous supply risk, and at the same time it adds noise and endogenous trading risk. The competitive entry equilibrium is characterized by excessive market entry and excessively volatile prices. A positive tax on entrants can decrease trader participation and volatility while increasing market efficiency. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.